2010
DOI: 10.1259/dmfr/16271087
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of ponticulus posticus in Indian orthodontic patients

Abstract: Objectives: The purpose of this study was to investigate the prevalence of complete ponticulus posticus in Indian orthodontic patients. Methods: The presence and types of ponticuli posticus were investigated on 858 lateral cephalograms. Results: Complete ponticulus posticus was found in 4.3% of the subjects studied with a male (5.33%) predominance over female in the population (3.76%). Conclusions: Ponticulus posticus is not a rare anomaly and the patient must be told of the implications and importance of dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
65
3
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(83 citation statements)
references
References 18 publications
7
65
3
8
Order By: Relevance
“…Although skeletal maturation evaluation 5 using the cervical vertebrae and its modified version are now commonly used to interpret the growth potential of young patients, inadequate attention is paid to the radiological anatomy of this region with a view to identifying pathology. 6 Knowledge of this anomaly is critical to surgeons performing posterior atlantoaxial fusions. 7 Since the treatment of atlantoaxial instability was revolutionized by the introduction of the C1LMS insertion, 8 many alterations to the method have been described and used successfully.…”
Section: Introductionmentioning
confidence: 99%
“…Although skeletal maturation evaluation 5 using the cervical vertebrae and its modified version are now commonly used to interpret the growth potential of young patients, inadequate attention is paid to the radiological anatomy of this region with a view to identifying pathology. 6 Knowledge of this anomaly is critical to surgeons performing posterior atlantoaxial fusions. 7 Since the treatment of atlantoaxial instability was revolutionized by the introduction of the C1LMS insertion, 8 many alterations to the method have been described and used successfully.…”
Section: Introductionmentioning
confidence: 99%
“…Especially when the head is moving, the neurodynamic process may lead to conditions cited above because of traction on the dura, and this can result in pain. 9,16 Wight et al 20 found increased presence of PP of the atlas in migraine sufferers. The presence of the PP has been related with shoulder and arm pain, neck pain, headaches, and dizziness.…”
Section: Clinical Significancementioning
confidence: 99%
“…The PP means "little posterior bridge" in Latin 3,6,[8][9][10][11][12][13][14][15][16][17][18] which describes an anomalous malformed bony bridge between the posterior portion of the superior articular process and the posterolateral portion of the superior margin of the posterior arch of the atlas. 9 The normal atlas ( Figure 1) is a ring-like structure consisting of two lateral masses connected by a short anterior arch and a longer posterior arch.…”
Section: Anatomymentioning
confidence: 99%
See 2 more Smart Citations